The mechanism of oxidative stress in asthenozoospermia and antioxidant strategies: a review - Mo, Linfeng; Wu, Hongmei; Zhang, Mingxue; Zhang, Peng; Peng, Wei; He, Yonghua; Gao, Feng (Frontiers in Endocrinology, 2025)
Asthenozoospermia, a leading cause of male infertility, is closely associated with oxidative stress (OS), which reflects an imbalance between reactive oxygen species (ROS) production and antioxidant capacity. ROS originate from both endogenous sources (e.g., inflammation and infection) and exogenous exposures (e.g., lifestyle and environmental pollutants). At physiological levels, ROS participate in key processes such as sperm proliferation, maturation, capacitation, acrosome reaction, and fertilization. However, excessive ROS become detrimental, damaging sperm membrane lipids, DNA integrity, and mitochondrial function, ultimately leading to reduced sperm motility and impaired fertility. A systematic understanding of the sources and mechanisms of ROS in asthenozoospermia is essential for developing targeted interventions. This review highlights the comprehensive integration of multiple ROS sources and their multi-level damaging effects, with a particular focus on mitochondrial dysfunction as a central mechanism in OS-induced sperm damage. Furthermore, we discuss the potential of antioxidant-based strategies and propose future directions for targeted therapies. This work aims to provide new insights into the treatment of asthenozoospermia and facilitate a shift from empirical management to mechanism-targeted therapies in clinical practice.